2010
DOI: 10.1108/13665621011053208
|View full text |Cite
|
Sign up to set email alerts
|

Learning gaps in a learning organization: professionals' values versus management values

Abstract: Purpose -The aim of this article is to challenge the concept of "the learning organization" as unproblematic and inherently good. Design/methodology/approach -The research looked at how teachers -as an example of public sector professionals in a work organization that claims to be a learning organization -view their conditions for learning. Findings -By using this approach, the normative values surrounding the concept of the learning organization were discussed. This approach identifies power-relations: i.e. w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
19
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
4
4

Relationship

2
6

Authors

Journals

citations
Cited by 17 publications
(23 citation statements)
references
References 25 publications
4
19
0
Order By: Relevance
“…For instance, in terms of how the workplace opens up for, or constrains, informal competence development, which is whether or not teachers can easily share with subject colleagues. These findings were neither new nor surprising; rather they were consistent with our previous studies (Jansson & Parding, 2011;Parding & Abrahamsson, 2010). Moreover, it could be argued that the local differences mirrored regional differentiation.…”
Section: Differentiated Conditionssupporting
confidence: 90%
See 2 more Smart Citations
“…For instance, in terms of how the workplace opens up for, or constrains, informal competence development, which is whether or not teachers can easily share with subject colleagues. These findings were neither new nor surprising; rather they were consistent with our previous studies (Jansson & Parding, 2011;Parding & Abrahamsson, 2010). Moreover, it could be argued that the local differences mirrored regional differentiation.…”
Section: Differentiated Conditionssupporting
confidence: 90%
“…Moreover, it could be argued that the local differences mirrored regional differentiation. In other words, in relation to our previous research (Jansson & Parding, 2011;Parding & Abrahamsson, 2010), as well as to the empirical data presented in this paper, it can be argued that the issue of context must be seen in a broader sense. The local and regional circumstances of a workplace must be considered when examining the conditions for competence development among welfare-sector professionals, as school choice and municipalization reforms seem to have complex consequences on various levels.…”
Section: Differentiated Conditionssupporting
confidence: 56%
See 1 more Smart Citation
“…In the sociology of professions, there has been a focus on clashes between various ideals for how to organise, plan, carry out and follow up work (Freidson, 2001;Evetts, 2006a;Evetts, 2006b). Indeed, in our own previous studies, we found that teachers Workplace learning in professional work may have a certain view of what is relevant to learn and how work should be organised to enable this, whereas the organisation (or the management) may have quite a different view (Parding, 2007;Parding and Abrahamsson, 2010;Jansson and Parding, 2011). We have identified how professionals enjoy teaching but remain unsatisfied with the way their work is organised, in addition to the conditions surrounding their work, as these conditions constrain the learning that they themselves identify as necessary; as a result, learning gaps were spotted (Parding, 2007;Parding and Abrahamsson, 2010;Jansson and Parding, 2011).…”
Section: Previous Research and Theoretical Frameworkmentioning
confidence: 97%
“…Interpretivist studies are based on a root metaphor or cultural perspective which considers a learning organisation as a metaphor and basically views the organisation itself as a type of culturea learning culture (Garavan, 1997;Parding & Abrahamsson, 2010).…”
Section: Conducting An Organisational Case Studymentioning
confidence: 99%